Tinjauan Kuat Geser Tanah Lempung Kecamatan Sukodono Kabupaten Sragen Yang Distabilisasi Dengan Bubuk Arang Kayu - Aji, Mukti, Qunik Wiqoyah, S.T., M.T (2016)
According to Prasetyo (2016) soil in Sukodono is clay with LL 85,73%, PL 24,69%, and PI 61,04%. Soil condition in dry season and rainy season and the easy damage road and cracking of building becomes the main problem of soil in Sukodono. Karaseran (2015) shell charcoal can improve water and air, carbon binder media, and decreasing swelling of soil because soil plasticity index. Based on the above research, so it used wood to stabilize with variation of a mixture of 5 % and 7.5%, and also it was done for treatment with 0, 3, and 7 to know its big effect of the percentage of mixture and the length of treatment with characteristic physic and mechanic properties of soil. Physical test of mixture soil was gotten of water content and plasticity increased whereas liquidity limit, shrinkage limit, plasticity index and passing sieve of No. 200 down. The original soil classification method based on AASHTO including group of A-7-5 and mixture of soil it includes group of A-7-6. Based on USCS the original soil and mixture soil are included CH. In the test of density the higher percentage of charcoal mixture, so it will be long for treatment of weight of dry volume decreasing but optimum content will be high. DST test showed the percentage of 5% cohesion wood charcoal powder tend decreasing but the percentage of 7,5% of cohesion value increasing. Angel of friction in the soil mixture tends to increase in the percentage of 5% wood charcoal powder, whereas the percentage 7,5% wood charcoal of inside friction decreased. The smallest value of cohesion is 0,548 kg/cm2 whereas the biggest inside friction is 21,400 in percentage of 7,5% wood charcoal powder with treatment 0 of day. The normal stress and shear stress soil mixture is lower than the original soil. The normal biggest stress is 3,858 kg/cm2 on original soil, the normal smallest stress is 3,215 kg/cm2 on percentage of 7,5% wood charcoal powder with treatment of 3 days. The shear biggest stress is 1,353 kg/cm2 on original soil, the smallest shear stress is 7,5% of wood charcoal powder with 3 days with 1,127 kg/cm2.